Electric Motorcycle Regulation Distribution Across Indonesian Regions: Distribusi Peraturan Sepeda Motor Listrik di Berbagai Wilayah Indonesia - Jessi Fatika Berliana; Mochammad Tanzil Multazam (Academia Open, 2025)
General Background: The rapid development of transportation technology has introduced electric motorcycles as an environmentally friendly alternative aligned with Indonesia’s carbon reduction commitments. Specific Background: Regulatory frameworks at national and regional levels are expected to provide legal certainty, safety standards, and technical feasibility for users of electric vehicles. Knowledge Gap: Despite numerous policies and incentives issued by the central government, the extent, distribution, and substantive coverage of regional regulations on electric motorcycles remain unclear and uneven. Aims: This study examines the development, distribution, and scope of electric motorcycle regulations across Indonesia and evaluates their capacity to ensure coherent governance. Results: A normative legal analysis of 1,639 regulations shows that only 0.73% explicitly address electric vehicles, while most rules continue to govern conventional transport, indicating limited regional commitment and fragmented policy adoption. Implementation of national initiatives at the local level is inconsistent, and many regional instruments remain advisory rather than binding. Novelty: The research provides a systematic mapping of regulatory distribution and thematic coverage across provinces and municipalities, revealing structural disparities between central policy direction and local legal frameworks. Implications: Strengthening harmonization between national and regional legislation and transforming local policies into imperative legal instruments are necessary to achieve uniform governance, stronger legal certainty, and safer deployment of electric motorcycles in Indonesia. Highlights: Explicit rules on battery-powered two-wheelers constitute a very small share of local legislation. Provincial and municipal frameworks display uneven thematic coverage and geographic distribution. Many local instruments function as guidance without enforceable obligations or sanctions. Keywords:Electric Motorcycles; Regional Regulation; Electric Vehicles; Legal Certainty; Traffic Law